Proparyation of Low frequency microwave in dusty Plasma - Baghdad Science Journal (مجلة بغداد للعلوم)
The numerical simulation for the low frequency waves in dusty plasma has been studied. The studying was done by taking two special cases depending on the direction of the propagation of the wave:First, when the propagation is parallel to the magnetic field K//B,this mode is called acoustic mode.Second,when K B this mode is called cyclotron mode.In addition, every one of the two modes divided into two modes depending on the range of the frequency.The Coulomb coupling parameter was studied, with temperature T,density of the dust particles Nd ,and the charge of the particle Qd.The low frequency electrostatic waves in dusty grains were studied. Also, the properties of ion-acoustic waves and ion-cyclotron waves are shown to modify even through the dust grains do not participate in the wave dynamics. If the dust dynamics induced in the analysis, new “ dust modes “ appear.